Determination of Rare Earth Elements Content in Hard Coal Type 31.1 - Baron Rafał (Management Systems in Production Engineering, 2020)
The aim of the article is to present the results of laboratory analyses determining the content of rare earth elements (REE) in hard coal type 31.1. Coal was extracted directly from the mining excavation located in the Upper Silesian Coal Basin. Mass spectrometry tests with ionization in inductively coupled plasma (ICP-MS), were aimed at the quantitative analysis of the share of REE in coal, taking into account the economic aspects of recovery of these elements. Fine ground hard coal samples and ashes obtained after coal burning were assessed for the rare earth elements concentration. Results of the rare earth elements concentration (lanthanum and cerium) in hard coal are similar in the values obtained in previous tests. The current analyses present higher concentration of europium or neodymium. The article also contains the concept of possible future research work, consisting in the recovery of rare earth elements using, among others, a classifying hydrocyclone.